Chinese Forensic Psychiatry: History, Development and Challenges - Li Xue; Yan-Wei Shi; James L Knoll; Hu Zhao (Wolters Kluwer Medknow Publications, 2015)
China has a long history of forensic psychiatry, which can be traced even back to Zhou dynasty (11 th century B.C.). However, modern forensic psychiatry has not been set up in China until the 1970s. After the interruption of Cultural Revolution of 1966-1976, there was a period of rapid development. In the past five years, a series of judicial identification system reforms have been taking place. In 2010, China had 225 forensic psychiatry agencies, 2,090 forensic psychiatry experts and 40,822 cases. The experts are organized within the separate agencies of psychiatric hospitals, universities, the Institute of Forensic Sciences of the Ministry of Justice and other forensic agencies. Apart from criminal forensic psychiatry, the experts are often asked to evaluate civil competency for the clients involved in civil litigation. Chinese forensic psychiatry has developed rapidly during the past 30 years, and formed the characteristics of its own under the special legal system. However, there is still much work for Chinese forensic psychiatrists to do for the future.